Português como Língua Estrangeira para tradutores em formação: uma análise da potencialidade da tradução de memes para o desenvolvimento da competência tradutória - Meléndez-Robles, Oscar Xavier (2025)
Teaching foreign languages in the training of professional translators and interpreters is a discussed and relevant topic in Translation Studies. This is evidenced by numerous studies that highlight the importance of differentiating between language teaching for communicative purposes and language teaching for specific purposes (Berenguer, 1996; Cruz, 2017; Gomes & Vasconcellos, 2020). In the case of teaching Portuguese to Spanish-speaking translators in training, the study of this language, through various pedagogical activities, should aim at developing more specific and specialized skills that can differentiate them from bilingual speakers (PACTE, 2003,2005; Gonçalves, 2015). Therefore, this article aims to describe the main components of memes, its possibilities in the foreign language classroom and its relevance in the development of students’ translation competences. To do so, we will analyze texts belonging to the meme textual genre (Almeida, 2020; Recuero, 2009) based on the concepts of adaptation and appropriation proposed by Hutcheon (2011) and Sanders (2016). This is an exploratory and applied study (Gil, 2023), following a qualitative approach. Through the analysis we were able to conclude that, given that the meme is a textual genre resulting from the combination of cultural and linguistic elements, analyzing the path of its creation and possible translation/adaptation contributes to the development of translation competence (TC).